MEMOSISIKAN SASTRA SIBER SEBAGAI LAHAN BARU DALAM PENELITIAN SASTRA MUTAKHIR DI INDONESIA - Rejo, Uman (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2014)
Cyber literature is literature that covers various genres of work submitted through the electronic media. Ideology contains in the literature cyber is postmodern ideology. Postmodern is difficult to be identified specifically, but the postmodern has common traits that always builds sorting binary opposition. In the current literary research, literary cyberspace is not a study, but rather a œstudy area. Cyber is the study of literature, not as a œperspective. As study materials, cyber literary phenomenon presents a unique, creative,and challanges a literary researcher. Therefore, the field is classified as current work, should use the latest research model, which is more significant if it is utilized.